Respuesta :

I hope this helps you
Ver imagen Аноним

Answer:

2

Step-by-step explanation:

Here, the given function is,

f(x) = The quantity of 4x plus 1, divided by 3

[tex]\implies f(x)=\frac{4x+1}{3}[/tex]

The steps that involve in finding the inverse of f(x) are as follows,

Step 1  : Replace f(x) by y,

[tex]y=\frac{4x+1}{3}[/tex]

Step 2 : Switch x and y,

[tex]x=\frac{4y+1}{3}[/tex]

Step 3 : Isolate y in the left side of the equation,

[tex]3x=4y+1[/tex]

[tex]-4y=1-3x[/tex]

[tex]y=\frac{1-3x}{-4}[/tex]

[tex]y=\frac{3x-1}{4}[/tex]

Step 4 : Replace y by [tex]f^{-1}(x)[/tex],

[tex]f^{-1}(x)=\frac{3x-1}{4}[/tex]

For x = 3,

[tex]f^{-1}(3)=\frac{3\times 3-1}{4}=\frac{9-1}{4}=\frac{8}{4}=2[/tex]

Hence, First option is correct.